2003
DOI: 10.1074/jbc.m309967200
|View full text |Cite
|
Sign up to set email alerts
|

Lec3 Chinese Hamster Ovary Mutants Lack UDP-N-acetylglucosamine 2-Epimerase Activity Because of Mutations in the Epimerase Domain of the Gne Gene

Abstract: Lec3Chinese hamster ovary (CHO) cell glycosylation mutants have a defect in sialic acid biosynthesis that is shown here to be reflected most sensitively in reduced polysialic acid (PSA) on neural cell adhesion molecules. To identify the genetic origin of the phenotype, genes encoding different factors required for sialic acid biosynthesis were transfected into Lec3 cells. Only a Gne cDNA encoding UDP-GlcNAc 2-epimerase:ManNAc kinase rescued PSA synthesis. In an in vitro UDP-GlcNAc 2-epimerase assay, Lec3 cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 46 publications
1
34
0
Order By: Relevance
“…This suggests that Large modifies N-glycans in Lec2 and Lec8 cells. Immunoblotting using a mAb against NCAM that is known to be N-glycosylated in CHO cells (64,65) showed that removal of N-glycans was efficiently achieved by the PNGase F treatment conditions used in this experiment. There was no effect of PNGase F on the ϳ38-kDa nonspecific band detected by IIH6.…”
Section: ␣-Dg Is Functionally Glycosylated By Overexpression Of Largementioning
confidence: 99%
“…This suggests that Large modifies N-glycans in Lec2 and Lec8 cells. Immunoblotting using a mAb against NCAM that is known to be N-glycosylated in CHO cells (64,65) showed that removal of N-glycans was efficiently achieved by the PNGase F treatment conditions used in this experiment. There was no effect of PNGase F on the ϳ38-kDa nonspecific band detected by IIH6.…”
Section: ␣-Dg Is Functionally Glycosylated By Overexpression Of Largementioning
confidence: 99%
“…These included Lec1, which lacks N-acetylglucosaminyltransferase 1, required for the synthesis of complex, and hybrid N-glycans Lec2, which lacks CMP sialyltransferase required for terminal glycan sialylation (21), and Lec 3.2.8.1 (LecR) a compound mutant that lacks both these enzymes in addition to the UDP-N-acetylglucosamine-2-epimerase required for sialic acid biosynthesis and the UDP-galactose transporter (33,34). Importantly, each of the mutant CHO transfectants expressed comparable levels of LYVE-1 at the surface as assessed by LYVE-1 immunostaining and flow cytometry, and each showed a significant change in mobility relative to wild type during SDS-PAGE (Fig.…”
Section: Identification Of Sialic Acid As An Inhibitory Moiety For Hamentioning
confidence: 99%
“…5), although in this case, CHO cells clearly bound more anti-PSA mAb than Lec23 cells. Lec2 CHO cells that are deficient in CMP-sialic acid transport expressed almost no PSA as shown previously (27,45,46). S440F was engineered into a full-length human GCS1 cDNA, the mutant cDNA was unable to rescue the Lec23 phenotype, and transfectants had almost no detectable ␣-glucosidase I activity in vitro despite overexpression of the cDNA.…”
Section: The Lec23 Mutant Reveals Activity Of Gcs1 Mutant Alleles Idementioning
confidence: 96%